Menggali Potensi ChatGPT pada Peran Tenaga Kesehatan: Looking into the Potential of ChatGPT in the Role Healthcare Professionals - Yuliyana, Rian; Daswito, Rinaldi (Poltekes Kemenkes Tanjungpinang, 2023)
This editorial article seeks to elucidate the potential of ChatGPT for healthcare professionals. ChatGPT is an advanced form of artificial intelligence that has the potential to offer significant advancements in addressing the pressing demands of society. The utilization of ChatGPT among health personnel might be seen as a phenomenon that yields both positive and bad consequences. One beneficial application is generating automated summaries of patient interactions and medical history, which can enhance the efficiency of medical documentation. Nevertheless, the utilization of ChatGPT in health care also presents ethical and legal issues. ChatGPT's performance may be inadequate in terms of context or nuance, both of which are crucial for ensuring safe and effective healthcare. ChatGPT represents a notable advancement in the field of information technology. However, it is crucial to carefully assess its application in the healthcare industry in the upcoming years, taking into account the need for equilibrium.